A study of the transition ice speed from intermittent crushing to frequency lock-in vibrations based on model-scale experiments - Owen, C.C. (author); Hendrikse, H. (author) (2019)
For the design of offshore structures in regions with ice-infested waters, the prediction of interaction between ice floe and support structure is essential. If the structure is vertically sided at the ice-structure interface, then ice-induced vibrations can develop. Recently, a dynamic icestructure interaction model has been developed and validation has been attempted based on dedicated experiments. This study extends the validation by investigating the capabilities of the analytical model in predicting the indentation speed at which transition from the intermittent crushing to frequency lock-in regime of ice-induced vibrations occurs with various input parameters. Implementation of these various input parameters seeks to address the challenge of adapting the analytical model from the reference input parameters to scenarios with other structural properties. Using these various input parameters, the analytical model can demonstrate accurate prediction of the transition ice speed from intermittent crushing to frequency lock-in vibrations as observed in the experiments when the mean global ice load in crushing is properly estimated. For the cases when the mean global ice load was not properly estimated, either unsuitable scaling between input parameters, undesirable behavior of the model ice during the experiments, or a combination thereof may be the cause. Overall, this study serves to establish the range of applicability for the analytical model in terms of accurate prediction of intermittent crushing and frequency lock-in vibrations between model ice and various structures. In addition, this study provides general trends about the effect of change of structural properties and initial conditions on the transition ice speed from intermittent crushing to frequency lock-in vibrations. Offshore Engineering